Social responsibility for its work under the corona pandemic - Benissad, Adra; Bouhemla, Salaheddine (Journal of Human Sciences, 2022)
Institutions play an important role in light of crises, epidemics and health emergencies, through their social responsibility in its various dimensions. The Covid-19 virus is a recent example of the institution’s contribution to alleviating its repercussions, especially for its workers and employees, and the accompanying economic recession due to quarantine, compulsory holidays and even the layoff of some workers. In addition to the impact of the Corona virus on the health aspect, it may have legal effects on the relationships that fall into this aspect, for example, the relationship of the institution with its workers.